Mindmade politics the cognitive roots of international climate governance - Milkoreit, Manjana (MIT Press, 2017)
Mindmade Politics takes a novel, interdisciplinary approach to understanding the complex and contentious dynamics of global climate politics. Manjana Milkoreit argues that integrating cognitive theories and international relations scholarship can yield valuable insights into multilateral cooperation (or the lack of it) on climate change and the process of negotiating climate agreements.